2015
DOI: 10.1016/j.jsat.2015.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Patient Violence Towards Counselors in Substance Use Disorder Treatment Programs: Prevalence, Predictors, and Responses

Abstract: Workplace violence disproportionately impacts healthcare and social service providers. Given that substance use and abuse are documented risk factors for the perpetration of violence, SUD treatment personnel are at risk for patient-initiated violence. However, little research has addressed SUD treatment settings. Using data nationally representative of the U. S., the present study explores SUD counselors’ experiences of violent behaviors perpetrated by patients. More than half (53%) of counselors personally ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 56 publications
(105 reference statements)
3
15
0
Order By: Relevance
“…Larger studies of workers in social service professions, often including CPS workers, identify the importance of demographics (Robson et al, 2014). Studies indicate that younger social service workers were more susceptible to violence than their older counterparts (Bride, Choi, Olin, & Roman, 2015;Jayaratne et al, 2004;Jayaratne, Vinokur-Kaplan, Nagda, & Chess, 1996;Ringstad, 2009;Spencer & Munch, 2003). For example, among a national sample of NASW members (N = 1,129), workers younger than 45 years experienced higher incidence of physical threats, verbal abuse, and sexual violence than their older counterparts (Jayaratne et al, 2004).…”
Section: Empirical Links Between Violence Susceptibility and Individual Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Larger studies of workers in social service professions, often including CPS workers, identify the importance of demographics (Robson et al, 2014). Studies indicate that younger social service workers were more susceptible to violence than their older counterparts (Bride, Choi, Olin, & Roman, 2015;Jayaratne et al, 2004;Jayaratne, Vinokur-Kaplan, Nagda, & Chess, 1996;Ringstad, 2009;Spencer & Munch, 2003). For example, among a national sample of NASW members (N = 1,129), workers younger than 45 years experienced higher incidence of physical threats, verbal abuse, and sexual violence than their older counterparts (Jayaratne et al, 2004).…”
Section: Empirical Links Between Violence Susceptibility and Individual Characteristicsmentioning
confidence: 99%
“…In terms of years of experience, Jayaratne et al (1996) found that social workers with less experience received more threats in the past year, but not more verbal or physical assaults, compared to workers with more experience. In samples of nursing personnel and substance abuse counselors, however, those with more experience encountered higher rates of verbal assaults and physical threats in the prior year (Bride et al, 2015;Campbell et al, 2011). Others found that years of training were not related to client-perpetrated violence among social service workers (Newhill, 1996;Winstanley & Hales, 2008).…”
Section: Empirical Links Between Violence Susceptibility and Individual Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The finding is in line with one study on the prevalence of patient threats towards SUD therapists in the USA, which reported that 84% of the participants had experienced directly some form of physical or psychological violence. The study also connected exposure to threats with work performance (Bride, Choi, Olin, & Roman, 2015), but did not report on the extent to which these experiences had occurred inside or outside clinical practice. Taken together, however, these numbers come across as high, and suggest SUD therapists may deal with threats as part of their everyday work lives.…”
Section: Patient Presenting Problemmentioning
confidence: 99%